Digital media and online buying considerations among generation Z in Malaysia / Mohd Remie Mohd Johan, Md. Azalanshah Md. Syed and Hamedi Mohd Adnan - Mohd Johan, Mohd Remie; Md. Syed, Md. Azalanshah; Mohd Adnan, Hamedi (Universiti Teknologi MARA, Perlis, 2022)
With the rapid development of technologies, the number of users accessing the Internet is rapidly increasing. Many businesses are now expanding their operations through digital media and online commerce platforms. Digital media commerce is defined as a business that is assisted by the Internet to increase the productivity and profitability of a company that revolves around e-commerce. Malaysia is one of the potential countries for digital media commerce as we have a large crowd of internet users which are dominated by the younger generation, especially Generation Z. These groups of people are technology savvy and are more prone to using the Internet. However, the growth in online purchases in Malaysia is still slow compared to the global trend. Hence, understanding their online purchase expectations and intentions can help businesses to improve their business strategy and cater strictly to Generation Z needs. It can also assist online retailers in providing customers with the same assurance that they have when they purchase from physical stores. From the findings, trust, security, and service quality are found to have significant influences on Generation Z’s online purchase intention